2000
DOI: 10.1034/j.1399-3011.2000.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of 15‐residue lactoferricin derivatives

Abstract: Lactoferricins are a class of antibacterial peptides isolated after gastric-pepsin digest of the mammalian iron-chelating-protein lactoferrin. For investigation of antibacterial activity, we prepared short synthetic derivatives of bovine, human, caprine, murine and porcine lactoferricins with 15-amino-acid residues of high sequence homology. The peptides corresponded to amino-acid residues 17-31 of the mature bovine lactoferrin. Only the bovine and caprine derivatives displayed measurable antibacterial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
128
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 40 publications
13
128
1
Order By: Relevance
“…A similar potentiation was observed with a tryptophan and arginine containing 15 residue lactoferricin derivatives, where a substitution for tryptophan in position 8 resulted in a 6-fold increase in antibacterial activity against E. coli. 29 An additional modification, in which the serine residues were replaced with threonine, resulted in the most potent peptide (7) in this series. Overall, the amphiphilic balance of cateslytin was gradually shifted to an increased hydrophobicity by the modifications.…”
mentioning
confidence: 99%
“…A similar potentiation was observed with a tryptophan and arginine containing 15 residue lactoferricin derivatives, where a substitution for tryptophan in position 8 resulted in a 6-fold increase in antibacterial activity against E. coli. 29 An additional modification, in which the serine residues were replaced with threonine, resulted in the most potent peptide (7) in this series. Overall, the amphiphilic balance of cateslytin was gradually shifted to an increased hydrophobicity by the modifications.…”
mentioning
confidence: 99%
“…It is noteworthy that reduction of the disulfide generates a linear peptide with similar activities that allowed the development of shorter synthetic derivatives with maintained properties (Bellamy et al, 1992). Much of the work was initially focused on the 11-and 15-residue fragments LfcinB 4-14 and LfcinB 1-15 , yielding important insights into the structural requirements (Kang et al, 1996;Strøm et al, 2000Strøm et al, , 2002Nguyen et al, 2005). Through these studies, it was shown that a combination of basicity and hydrophobicity, mainly in the form of arginine and tryptophan, is necessary for activity (Haug and Svendsen, 2001;Strøm et al, 2002Strøm et al, , 2003.…”
mentioning
confidence: 99%
“…As a result, further study was given to the isolation of the lactoferricin peptide produced in vivo by digestion of bovine lactoferrin (27,40). More recently, additional work has focused upon the identification of key antimicrobial segments and enhancement of the activity of the various shorter synthetic human lactoferricin (LfcinH) peptide analogs by using amino acid substitutions and various activity assays (7,10,11,28,30,37,42,47). These studies have established not only that LfcinH has antimicrobial, antiviral, and antifungal activities but also that it is capable of stimulating the immune system and neutralizing endotoxin.…”
mentioning
confidence: 99%